The relationship between time of delivery and composite outcomes in women who sent to the intermediate intensive care unit after delivery (Annals of Medical Research, 2022)
Aim: In this study, we evaluated the effects of delivery time on maternal-fetal outcomes by evaluating patients who were taken to the gynecological intermediate intensive care unit according to their delivery hours.Materials and Methods: This study cohort included 292 women aged 18-45 years, whom we followed up in the postpartum gynecological intermediate intensive care unit. We divided the patients into three groups according to the time they gave birth. Those who gave birth between 08:00-16.00 formed group1, those who gave birth between 16:00-24:00 group2, and those who gave birth between 24:00-08:00 formed group 3. We compared all collected data between groups.Result: Hysterectomy (45(36%)) and blood transfusion (35(28%)) rates in the first group were higher than the other groups (p
Keywords: Time of delivery; Composite outcomes; Delivery; Intermediate intensive care unit